2021
DOI: 10.3390/agriculture11050410
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Evaluation of the FAO AquaCrop Model for Canola (Brassica napus) under Varied Moistube Irrigation Regimes

Abstract: The AquaCrop model was calibrated and validated for canola (Brassica napus) under Moistube irrigation (MTI) and various water regimes [(i) 100%, (ii) 75%, and (iii) 55% of crop water requirement (ETc)] over two seasons, 2019 and 2020. The normalised root mean square (nRMSE), Model Efficiency (EF), R2, and the Willmot’s index of agreement (d) statistics were used to evaluate the model’s efficiency in simulating biomass (B), canopy cover (CC), yield (Y), and harvest index (HI). The calibration results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
1
7
1
Order By: Relevance
“…In a greenhouse experiment on cherry tomato with plastic film mulch [28], Cheng et al [28] also observed an overestimation of SWC. However, this result contradicts with the result of [39] on maize, [23,40] on Canola, who suggests the Aqua-Crop model performed well on SWC.…”
Section: Performance Evaluation Of Aquacropcontrasting
confidence: 90%
See 1 more Smart Citation
“…In a greenhouse experiment on cherry tomato with plastic film mulch [28], Cheng et al [28] also observed an overestimation of SWC. However, this result contradicts with the result of [39] on maize, [23,40] on Canola, who suggests the Aqua-Crop model performed well on SWC.…”
Section: Performance Evaluation Of Aquacropcontrasting
confidence: 90%
“…This shows that applying stage deficit irrigation improves yield and water productivity compared to FI [8]. This result is also confirmed by [23,37,38,39,40,41]; the best WP was observed at the lowest irrigation depth.…”
Section: Validation Parameter Of Measured and Simulatedsupporting
confidence: 79%
“…It is cultivated on 2418 thousand hectares in Pakistan, which produce 2256 thousand tons of seeds and 374 thousand tons of oil [3]. It is an inexpensive oil that helps individuals recover from malnutrition and improves their health, making it ideal for populations residing in developing nations [12]. Climate extremes, such as heat and drought stress [13][14][15], soil salinity [16], limited light availability [17], and waterlogging [18], are the major constraints significantly reducing the yield and oil quality of oilseed rape.…”
Section: Introductionmentioning
confidence: 99%
“…The AquaCrop model is underpinned by two sets of parameters, conservative and non-conservative, where the former does not change with time and its applicable over a large spatial variation (i.e., water stresses on crop growth and development), the latter changes with time, management practices and location (i.e., sowing date, sowing method and density, and plant phenology) (Dirwai et al, 2021). Crop variables were parametrized on AquaCrop based on field observations on crop development, including plant phenology, made by the Ministry of Agriculture, Forestry and Fisheries (MAFF) of Cambodia and shared with FAO for the purpose of this study (Table 1).…”
Section: Crop Datamentioning
confidence: 99%